2005
DOI: 10.3171/spi.2005.2.1.0055
|View full text |Cite
|
Sign up to set email alerts
|

Role of granulocyte—macrophage colony—stimulating factor in preventing apoptosis and improving functional outcome in experimental spinal cord contusion injury

Abstract: Object. Granulocyte—macrophage colony—stimulating factor (GM-CSF) is a potent hemopoietic cytokine that stimulates stem cell proliferation in the bone marrow and inhibits apoptotic cell death in leukocytes. Its effects in the central nervous system, however, are still unclear. The present study was undertaken to determine if GM-CSF can rescue neuronal cells from apoptosis and improve neurological function in a spinal cord injury (SCI) model. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 25 publications
2
69
1
Order By: Relevance
“…Support for a neuroprotective action of GM-CSF in the CNS also comes from another disease model, spinal cord contusion (Ha et al, 2005). The authors could show effects of GM-CSF treatment (20 mg/day for 5 days) on the improvement of the BBB score, and show decreased apoptosis in the spinal cord.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Support for a neuroprotective action of GM-CSF in the CNS also comes from another disease model, spinal cord contusion (Ha et al, 2005). The authors could show effects of GM-CSF treatment (20 mg/day for 5 days) on the improvement of the BBB score, and show decreased apoptosis in the spinal cord.…”
Section: Discussionmentioning
confidence: 70%
“…Granulocyte-macrophage colony-stimulating factor receptor expression has been noted in neurons in the fetal human brain (Dame et al, 1999), supporting the notion that GM-CSF likely also has a neurodevelopmental role. Neuronal staining has been reported in the adult spinal cord (Ha et al, 2005). Recently, presence of the GM-CSF receptor on hypothalamic neurons in the adult brain has been described (Reed et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed significant locomotor recovery in the EpoSV-GM-CSF-transfected NSC-transplanted group, a new development in preceding reports that have stated that only GM-CSF could enhance locomoter function in the spinal cord contusion injury. 45 Because of the low survival rate of NSC in the SCI, 20,21 in this study, we attempted to demonstrate NSC survivalenhancement by hypoxia-induced GM-CSF as a result of locomoter function improvement. We concluded that the enhanced in vivo recovery effect had been caused by two indistinguishable factors: hypoxia-induced GM-CSF, and GM-CSF-induced transplanted cell survival and differentiation in the SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Ha et al first demonstrated that GM‐CSF improves functional outcome after rat contusive SCI 46. The improvement is probably due to the prevention of apoptosis of the cells, including neurons,46 via reduction of the expression of the proapoptotic proteins p53, p21, and Bax, and induction of nucleophosmin‐144 and the antiapoptotic protein B‐cell lymphoma 2 (Bcl‐2) 45.…”
Section: Roles Of Inflammatory Cytokines In Sci Repairmentioning
confidence: 99%
“…The improvement is probably due to the prevention of apoptosis of the cells, including neurons,46 via reduction of the expression of the proapoptotic proteins p53, p21, and Bax, and induction of nucleophosmin‐144 and the antiapoptotic protein B‐cell lymphoma 2 (Bcl‐2) 45. Additionally, GM‐CSF increased BDNF expression by macrophages, and subsequently stimulated axonal regeneration 49.…”
Section: Roles Of Inflammatory Cytokines In Sci Repairmentioning
confidence: 99%